Thoracoscopic surgery for congenital diaphragmatic hernia in neonates: Should it be the first choice? - Liu, Rui; Zheng, Zebing; Tang, Chengyan; Zhang, Kaizhi; Du, Qing; Gong, Yuan; Zhu, Daiwei; Xia, Xingrong; Zhou, Wankang; Huang, Lu; Liu, Yuanmei; Jin, Zhu (Frontiers in Pediatrics, 2022)
Objective: Congenital diaphragmatic hernia (CDH) is an uncommon but potentially life-threatening surgical condition in neonates. Surgery can be performed by either open or thoracoscopic techniques. In this study, we compared the clinical efficacy, safety, and effectiveness of thoracoscopic and open CDH repair. Methods: A retrospective review of neonates with CDH who underwent operations at our hospital from 2013 to 2021 was performed. The various perioperative parameters were compared between neonates undergoing thoracoscopic and open surgery. Results: There were 50 neonates in this study (37 in the thoracoscopic group and 13 in the open group). Thoracoscopic surgery was associated with significantly shorter hospital stay (13.32 vs. 18.77 days, p<0.001); shorter duration of postoperative mechanical ventilation (3.70 vs. 5.98 days, p<0.001); early feeding (4.34 vs. 7.46 days, p<0.001); and shorter time to reach optimal feeding (8.21 vs. 13.38 days, p<0.001). There was one postoperative death in the open group and no death in the thoracoscopic group. The median follow-up time of the two groups was 23.8 months. Thoracoscopic surgery was associated with lower recurrence rates, but the difference was not statistically significant (2.7% vs. 7.7%, p=0.456). Conclusion: Thoracoscopy CDH repair, a safe and effective surgical technique for neonates, has better cosmesis, faster postoperative recovery, and a lower recurrence rate than other procedures. It can be considered the first choice for CDH treatment for neonates among experienced surgeons.